`2/3 - 3/8 = (2xx8)/(3xx8) - (3xx3)/(8xx3) = 16/24 - 9/24 =(16-9)/24 = 7/24`
\(\dfrac{2}{3}-\dfrac{3}{8}=\dfrac{16-9}{24}=\dfrac{7}{24}\)
\(\dfrac{2}{3}-\dfrac{3}{8}=\dfrac{16}{24}-\dfrac{9}{24}=\dfrac{7}{24}\)
`2/3 - 3/8 = (2xx8)/(3xx8) - (3xx3)/(8xx3) = 16/24 - 9/24 =(16-9)/24 = 7/24`
\(\dfrac{2}{3}-\dfrac{3}{8}=\dfrac{16-9}{24}=\dfrac{7}{24}\)
\(\dfrac{2}{3}-\dfrac{3}{8}=\dfrac{16}{24}-\dfrac{9}{24}=\dfrac{7}{24}\)
\(\dfrac{3}{7}\) + 4 = ?
\(\dfrac{5}{9}\) x 3 = ?
\(\dfrac{7}{8}\) - \(\dfrac{2}{9}\)= ?
5 - \(\dfrac{3}{4}\)= ?
\(\dfrac{5}{7}\) : 6 = ?
\(\dfrac{5}{6}\) x \(\dfrac{2}{7}\)= ?
3 + \(\dfrac{3}{4}\)= ?
\(\dfrac{3}{5}x\dfrac{4}{8}\) = ?
5 : \(\dfrac{3}{8}\)= ?
Mong mn trả lời
\(\dfrac{2}{5}\) x \(\dfrac{3}{4}-\dfrac{1}{8}\) \(= \)
\(\dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\)
\(\dfrac{9}{20}-\dfrac{3}{5}\) x \(\dfrac{1}{4}\)\(= \)
\(\dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}\)\(=\)
Tính :
a) 7 x \(\dfrac{3}{14}\) - \(\dfrac{1}{14}\) b) \(\dfrac{3}{2}\) + \(\dfrac{7}{4}\) x \(\dfrac{2}{5}\)
c) \(\dfrac{9}{8}\) : 3 + \(\dfrac{7}{8}\) : 3 d) 2 : \(\dfrac{3}{4}\) - \(\dfrac{5}{8}\) x \(\dfrac{4}{3}\)
\(\dfrac{3}{5}+\dfrac{1}{2}+\dfrac{8}{15}\)
\(\dfrac{6}{9}+\dfrac{14}{18}-\dfrac{5}{6}\)
\(\dfrac{9}{20}-\dfrac{3}{5}:\dfrac{4}{1}\)
\(\dfrac{1}{6}+\dfrac{2}{3}\) x \(\dfrac{8}{9}\)
a.\(\dfrac{3}{4}+\dfrac{5}{6}\) b.\(\dfrac{5}{18}\times\dfrac{10}{3}\) c.\(\dfrac{2}{3}-\dfrac{3}{8}\) d.\(\dfrac{8}{5}\div\dfrac{3}{4}\)
\(\dfrac{2}{5}\) + \(\dfrac{5}{6}\)
\(\dfrac{11}{10}\) - \(\dfrac{2}{5}\) : \(\dfrac{2}{3}\)
\(\dfrac{2}{3}\) - \(\dfrac{3}{8}\)
\(3-\dfrac{8}{13}-\dfrac{2}{13}-\dfrac{3}{13}\)
\(\dfrac{8}{10}+\dfrac{1}{5}-\dfrac{1}{4}-\dfrac{15}{20}\)
Tính:
a) \(\dfrac{6}{7}\times\dfrac{2}{3}=...\)
b) \(\dfrac{3}{8}\times\dfrac{3}{8}=...\)
\(\dfrac{1}{3}+\dfrac{2}{3}+\dfrac{4}{3}+\dfrac{19}{3}=\) | \(\dfrac{3}{4}+\dfrac{4}{4}+\dfrac{5}{4}+\dfrac{6}{4}+\dfrac{x}{2}+\dfrac{8}{2}+\dfrac{9}{4}\)= |
HELP
Bài1 tính:
a)\(\dfrac{2}{5}\)+\(\dfrac{5}{12}\); b)\(\dfrac{2}{3}\) - \(\dfrac{3}{8}\); c)\(\dfrac{3}{7}\) ✖ \(\dfrac{4}{9}\); d) \(\dfrac{11}{10}\) - \(\dfrac{2}{5}\) ː \(\dfrac{2}{3}\)